Procesamiento de yuca en Colombia: La produccion y uso de harina de yuca para consumo humano. Informe de avance periodo noviembre 1984-octubre 1985 - International Center for Tropical Agriculture; Universidad del Valle (International Center for Tropical Agriculture, 1986)
The progress made during the 1st yr of an interinstitutional collaborative project among CIAT, the Instituto de Investigaciones Tecnologicas, and the U. del Valle, on the processing, production, and use of CF, is described. The 3 main areas of research were: economic studies, design and development of the processing plant, and breadmaking trials. Furthermore, a program of activities in the 3 areas is given for the 2nd yr, as well as a statement of past and projected expenses. Economic and technical information was partially generated to determine the feasibility of a CF industry on the Atlantic Coast of Colombia. In the area of economic studies, basic information was collected on macro-analyses of the wheat market, cassava production and commercialization (survey), wheat mills (survey), bakeries and consumers (survey), and on-farm cassava production trials. Equipment was adapted and developed for small-scale rural processing of cassava roots for flour. Trials on washing, peeling, chipping, drying, milling, and packing and storage were carried out, and the results are discussed. Results of breadmaking trials using composite flours are also presented. (CIAT)